2016
DOI: 10.1088/1367-2630/18/4/043036
|View full text |Cite
|
Sign up to set email alerts
|

Single-electron entanglement and nonlocality

Abstract: Motivated by recent progress in electron quantum optics, we revisit the question of single-electron entanglement, specifically whether the state of a single electron in a superposition of two separate spatial modes should be considered entangled. We first discuss a gedanken experiment with singleelectron sources and detectors, and demonstrate deterministic (i. e. without post-selection) Bell inequality violation. This implies that the single-electron state is indeed entangled and, furthermore, nonlocal. We the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 65 publications
0
61
0
1
Order By: Relevance
“…In the second line, we indicate the number of particles localized with each party, i.e., false|1A,0B=false|1Afalse|0B and false|0A,1B=false|0Afalse|1B. Together with the Quantum Correlations Group in Geneva, we have recently demonstrated that this state is entangled and the entanglement can be experimentally detected . At first, this might not be obvious, since the local operations that Alice and Bob can perform are constrained by parity and charge super‐selection rules.…”
Section: Dynamic Entanglement Generationmentioning
confidence: 99%
See 4 more Smart Citations
“…In the second line, we indicate the number of particles localized with each party, i.e., false|1A,0B=false|1Afalse|0B and false|0A,1B=false|0Afalse|1B. Together with the Quantum Correlations Group in Geneva, we have recently demonstrated that this state is entangled and the entanglement can be experimentally detected . At first, this might not be obvious, since the local operations that Alice and Bob can perform are constrained by parity and charge super‐selection rules.…”
Section: Dynamic Entanglement Generationmentioning
confidence: 99%
“…The entanglement in Eq. can nevertheless be detected using a copy of the state . Since two fermions cannot occupy the same state, we introduce an additional degree of freedom that we denote by σ=±.…”
Section: Dynamic Entanglement Generationmentioning
confidence: 99%
See 3 more Smart Citations